Construction of Ni3S2-NixPy/NF@NiFe LDH with heterogeneous interface to accelerate catalytic kinetics of overall water splitting - Chengdong Han; Zhengtong Ji; Yongfu Zhu; Xue Yao; Peng Chen; Manying Guo; Lijun Zhao; Xingyou Lang; Qing Jiang (Materials Research Letters, 2022)
Reasonable design of a kind of non-noble metal catalyst with high catalytic performance, good stability and low cost is of great significance to realize the overall water splitting. Herein, a bottom-up method is proposed to synthesize NiFe layered double hydroxides (NiFe LDHs) coated sulfide/phosphide heterostructure on the nickel foam (Ni3S2-NixPy/NF@NiFe LDH) through hydrothermal method combined with electrodeposition. Low overpotentials of only 248 and 298 mV are required to achieve the current densities of 50 and 100 mA cm−2 for OER. Meanwhile, the HER performance only needs 137 mV at a current density of 10 mA cm−2.